US-Japan Trade Friction - Mason, T. David. author. aut Link
XIV, 228 p.
Keywords: Relations between Japan and the US remain strong, and government-to-government relations continue to be productive. However, complaints can be heard. This volume reflects these sentiments and emphasizes the need to promote closer ties and greater understanding between the US and Japan.